Ethno-physics: The Exploration of Kloso Handicraft as a Local Culture in Rumpuk Village - Afaurina Indriana Safitri; Nadi Suprapto; Khoirun Nisa' (Kawalu: Journal of Local Culture, 2023)
Kloso is a type of local wisdom in the form of woven pandan leaves that can be used as a learning medium to make it easier for students to understand physics concepts. The author realizes that this research, especially the exploration of physics concepts in local wisdom, has limitations. Therefore, it is necessary to carry out activities to explore the concepts of physics and local wisdom in each process of making Kloso in. This study aims to explore and analyze the physics concepts contained in each stage of making Kloso. This research is a qualitative research using data triangulation methods: interview, observation, and literature studies. The results showed that there was a correlation between Kloso’s making stage and physics concept. The physics concepts contained in Kloso such as energy, momentum, parabolic motion, Newton's Laws, pressure, and heat changes. Thus, this local wisdom can be used as a medium of learning, especially in the field of physics, to increase the understanding of physics that is integrated into ethnoscience (Ethno-physics), a science that is actually implemented in every activity of daily life.